Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites. (15th May 2023) - Li, Shiyu; Yang, Lin; Wu, Jialong; Yao, Linlin; Han, Deming; Liang, Yong; Yin, Yongguang; Hu, Ligang; Shi, Jianbo; Jiang, Guibin
Highlights: A recyclable MoS2 /Fe3 O4 was developed to remediate mercury-contaminated water. The MoS2 /Fe3 O4 exhibited excellent adsorption capacity and selectivity for Hg(II). The hierarchical microstructure improved the accessibility of sulfur active sites. The application potential of MoS2 /Fe3 O4 was verified in various real water matrices. The mechanism of Hg(II) immobilization was mainly owning to surface coordination. Abstract: Developing practical and cost-effective adsorbents with satisfactory mercury (Hg) remediation capability is indispensable for aquatic environment safety and public health. Herein, a recyclable hierarchical MoS2 /Fe3 O4 nanocomposite (by in-situ growth of MoS2 nanosheets on the surface of Fe3 O4 nanospheres) is presented for the selective removal of Hg(II) from aquatic samples. It exhibited high adsorption capacity (∼1923.5 mg g   −1 ), fast kinetics ( k 2 ∼ 0.56 mg g   −1 min −1 ), broad working pH range (2–11), excellent selectivity ( K d > 1.0 × 10 7  mL g   −1 ), and great reusability (removal efficiency > 90% after 20 cycles). In particular, removal efficiencies of up to ∼97% for different Hg(II) concentrations (10–1000 μg L   −1 ) in natural water and industrial effluents confirmed the practicability of MoS2 /Fe3 O4 . The possible mechanism for effective Hg(II) removal was discussed by a series of characterization analyses, which was attributed to the alteration of the MoS2 structure and the surface coordination of Hg-S. The accessibility of surface sulfur sites and the diffusion of Hg(II) in the solid-liquid system were enhanced due to the advantage of the expanded interlayer spacing (0.96 nm) and the hierarchical structure. This study suggests that MoS2 /Fe3 O4 is a promising material for Hg(II) removal in actual scenarios and provides a feasible approach by rationally constructing hierarchical structures to promote the practical applications of MoS2 in sustainable water treatments. Graphical abstract: Image, graphical abstract